2020
DOI: 10.12659/msm.922860
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Glucose and High-Fat Condition on Estrogen Receptor- and Sexual Precocity-Related Genes in GT1-7 Cells

Abstract: Departmental sources Background:This study was designed to investigate the effect of high-glucose and high-fat condition on estrogen receptorand sexual precocity-related genes in GT1-7 cells. Material/Methods:In this study, CCK8 was used to detect cell viability, and TUNEL assay was used to detect apoptosis levels of GT1-7 cells after treatment with glucosamine and palmitate. The expression level of GnRH was measured by ELISA and RT-qPCR. RT-qPCR and Western blot were used to detect the expression of ERb, CD36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…ICPP can lead to metabolic abnormalities and affect the central nervous system. It has been shown that a HG and HF diet can affect the expression of ER- and PP-related genes in hypothalamic cells ( 7 ). In the present study, a HG- and HF-induced GT1-7 mouse hypothalamic cell line was used as the PP in vitro model to simulate the physiological environment of PP in the body, as previously described ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ICPP can lead to metabolic abnormalities and affect the central nervous system. It has been shown that a HG and HF diet can affect the expression of ER- and PP-related genes in hypothalamic cells ( 7 ). In the present study, a HG- and HF-induced GT1-7 mouse hypothalamic cell line was used as the PP in vitro model to simulate the physiological environment of PP in the body, as previously described ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a HG and HF diet can affect the expression of ER- and PP-related genes in hypothalamic cells ( 7 ). In the present study, a HG- and HF-induced GT1-7 mouse hypothalamic cell line was used as the PP in vitro model to simulate the physiological environment of PP in the body, as previously described ( 7 ). The role of LKB1 in the progression of PP in this in vitro model was also explored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations